Meta-analysis on Studies of Deviant Marketing Behaviors: Past, Present and Future - Zahra Ahmadi Alvar; Davood Feiz; Meysam Modarresi (‫مدیریت بازرگانی)
Objective In recent years, one emerging area of interest for researchers has been the study of deviant behaviors in marketing. The objective of this article is to provide an in-depth understanding of the progress in marketing deviant behavior studies by conducting a comprehensive review of scientific articles in this field, utilizing text-mining methodologies.